2007
DOI: 10.1124/dmd.106.013862
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal First-Pass Metabolism via Carboxylesterase in Rat Jejunum and Ileum

Abstract: ABSTRACT:To determine the activity of a major intestinal esterase in the first-pass hydrolysis of O-isovaleryl-propranolol (isovaleryl-PL), a model ester compound, rat intestinal jejunum and blood vessels were perfused simultaneously after inhibition of a carboxylesterase (CES) by bis-p-nitrophenyl phosphate (BNPP). BNPP specifically inhibits approximately 90% of CES activity without influencing aminopeptidase activity or the transport of L-leucyl-p-nitroanilide and p-nitroaniline, nonester compounds. When iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…The perfusates from the luminal segment and vascular outflow were collected at appropriate points. A CES-inhibited condition was achieved by preperfusion with BNPP (400 M) for 40 min, in accordance with a previously reported methodology (Masaki et al, 2007). The chemical degradation of temocapril was negligible during the perfusion experiment.…”
Section: Methodsmentioning
confidence: 68%
See 3 more Smart Citations
“…The perfusates from the luminal segment and vascular outflow were collected at appropriate points. A CES-inhibited condition was achieved by preperfusion with BNPP (400 M) for 40 min, in accordance with a previously reported methodology (Masaki et al, 2007). The chemical degradation of temocapril was negligible during the perfusion experiment.…”
Section: Methodsmentioning
confidence: 68%
“…Masaki et al (2007) proposed a methodology whereby rat intestinal CES was inhibited by BNPP; BNPP irreversibly inhibits all CES isozymes with K i values of 44.9 Ϯ 4.95 nM in rat jejunal S9 but has no effect on other hydrolases such as aminopeptidase. Masaki et al (2007) also established that nearly complete inhibition of CES is obtained by preperfusion with BNPP (400 M for 40 min). More recently, Ohura et al (2010) reported that BNPP affects neither active transport, e.g., p-glycoprotein, peptide, and organic anion transporters, nor passive diffusion in Caco-2 cell monolayers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intestinal cellular S9 fractions were prepared as described previously (Masaki et al, 2007), with modifications. In dmd.aspetjournals.org brief, the small intestines were excised and rinsed with chilled 1.15% KCl.…”
Section: Methodsmentioning
confidence: 99%